Bradycardia in the trained athlete is attributable to a downregulation of a pacemaker channel in the sinus node - D`Souza, A.; Sharma, S.; Boyett, M. R. (The Journal of Physiology, 2015)
If the bradycardia is not the result of high vagal tone, what is the underlying mechanism? The sinus node is the `Cinderella` of the heart and is under-studied as compared to the working myocardium and, therefore, when discussing possible causes of change in sinus node function the investigator has had little to guide them.